EDUKASI PENANGANAN BENIH CABAI KATOKKON PADA KELOMPOK WANITA TANI LEMBANG SANDANA, TANA TORAJA - Karuru, Perdy; Taufik, Muhammad; Kannapadang, Sepsriyanti; Pasanda, Afra Andre; Gusnawaty HS, Gusnawaty HS; Aku, Achmad Selamet (Universitas Tanjungpura, 2024)
The katokkon chili plant (Capsicum chinense Jacq.) is a crop commodity that has high economic value. This type of chili is suitable for planting in high-altitude areas such as the Tanah Toraja region. However, its productivity is still low compared to its production potential, which can reach tens of tons/ha. The low level of knowledge and skills of chili farmers is one of the problems in increasing the productivity of katokkon chilies. The service aims to educate katokkong chili farmers in Lembang Sandana on good seed treatment. The methods used are outreach activities, education, and training on how to treat katokkong chili seeds and make appropriate chili seedling media. Pre- and post-tests were carried out to measure the level of success in implementing activities. Socialization carried out with target partners and collaboration resulted in collaborative support by the head of the Lembang and target partners for implementing kosabangsa. The results of education and training show that 94% of target partners have understood and implemented seed treatment methods such as using growth regulators, soaking in warm water (hot water treatment) and sowing seeds in rockwool media, as well as making growing media using a ratio of buffalo manure. , top soil and husk (1:2:1, v/v) appropriately. The education carried out by the kosabangsa service team has increased the level of knowledge and skills of farmers regarding how to treat katokkon seeds properly